Organisational learning and effectiveness - Denton, John, 1971- (Routledge, 1998)
Based upon indepth case studies of companies such as Coca-Cola and 3M this book is an original and comprehensive analysis of learning organisations. Includes interviews with over seventy managers and eployees.